2008
DOI: 10.1186/1471-2474-9-30
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between previous hamstring injury and the concentric isokinetic knee muscle strength of irish gaelic footballers

Abstract: Background: Hamstring injury is one of the most common injuries affecting gaelic footballers, similar to other field sports. Research in other sports on whether residual hamstring weakness is present after hamstring injury is inconsistent, and no study has examined this factor in irish gaelic footballers. The aim of this study was to examine whether significant knee muscle weakness is present in male Irish gaelic footballers who have returned to full activity after hamstring injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
1
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 32 publications
3
35
1
7
Order By: Relevance
“…ehabilitation and prevention strategies for hamstring injuries have focused on muscle strength and flexibility, 5,16,45 with more recent investigations and recommendations suggesting that neuromuscular control 32,49 and sports-specific skills and balance may also be important. 39 Isokinetic dynamometry is commonly used to assess quadriceps and hamstring muscle strength as a potential risk factor for future injury or for residual deficits following hamstring injuries.…”
mentioning
confidence: 99%
“…ehabilitation and prevention strategies for hamstring injuries have focused on muscle strength and flexibility, 5,16,45 with more recent investigations and recommendations suggesting that neuromuscular control 32,49 and sports-specific skills and balance may also be important. 39 Isokinetic dynamometry is commonly used to assess quadriceps and hamstring muscle strength as a potential risk factor for future injury or for residual deficits following hamstring injuries.…”
mentioning
confidence: 99%
“…In a two year follow-up in a cohort of ACL injured individuals, Grindem et al demonstrated that many individuals (23% to 35%) continued to have knee flexion and extension strength deficits with percentages of individuals with deficits similar to the current study or higher. O'Sullivan and colleagues assessed isokinetic strength in a group of Gaelic footballers who had previously suffered hamstring injuries [37]. The Gaelic footballers' previous injured extremity had significantly lower hamstrings/quadriceps strength ratios and weaker hamstrings when matched for limb dominance.…”
Section: Discussionmentioning
confidence: 99%
“…It is not unusual to see persistent deficits in strength following injury. For example, previous injury to the meniscus, the hamstrings musculature, and the anterior cruciate ligament (repaired or conservatively managed) results in persistence strength deficits in a significant percentage of individuals [35][36][37]. Stensrud et al examined individuals with degenerative meniscal tears and demonstrated significant side-to-side deficits in quadriceps strength and with half of the group demonstrating significant "clinically relevant impairments" (greater than 10%) [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atualmente, a medida de força muscular tem sido utilizada para otimizar os resultados de atletas em competições e avaliar o balanço muscular tanto em atletas e indivíduos não atletas. O balanço muscular, determinado pela razão entre a musculatura agonista e a antagonista de cada movimento, é um elemento importante para a eficiência da movimentação articular; o conhecimento desse parâmetro tem sido utilizado em programas de prevenção de lesões musculares, tendíneas e articulares (7)(8)(9)(10) . A mensuração da força muscular pode ser realizada a partir de métodos que utilizem diferentes modos de contração: isométrica, isocinética e isotônica.…”
Section: Introductionunclassified